Integrating Global Citizenship Education into Pancasila Education: Curriculum Review in Indonesia - Anggaraini, Rita; Habibah, Siti Maizul; Istianah, Anif; Sari, Beti Indah; Listyaningsih, Listyaningsih; Harmanto, Harmanto (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2025)
This article examines the integration of Global Citizenship Education (GCE) into Indonesia’s civic education curriculum to promote multicultural attitudes among students. Drawing on curriculum reviews, recent policy initiatives, and scholarly analyses, the study highlights how Pancasila Education has increasingly incorporated themes of intercultural dialogue, environmental stewardship, human rights, and collaborative problem-solving. Teachers and school culture emerge as key drivers in translating these values into practice, while regional disparities and limited professional development remain significant challenges. The discussion underscores the pivotal role of Pancasila Indonesia’s national ideology as a moral and philosophical foundation that aligns local wisdom with universal principles of peace, justice, and human dignity. Each of Pancasila’s five principles provides a bridge between national identity and global responsibilities, ensuring that GCE strengthens rather than dilutes cultural heritage. Findings suggest that a Pancasila-based GCE framework fosters tolerant, empathetic, and critically minded learners capable of engaging with complex global issues while maintaining strong national cohesion. The article concludes with recommendations for enhancing teacher training, enriching experiential learning opportunities, and addressing regional implementation gaps to fully realize the transformative potential of Global Citizenship Education in Indonesia